Does People's Bank of China communication matter? Evidence from stock market reaction - Hamza Bennani (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper tests whether the People's Bank of China's communication affects expectations of market participants and matters as a monetary policy instrument. For that purpose, we first rely on a computational linguistic tool to measure the tone of PBC speeches and second, we use a high frequency methodology to estimate the effect of tone on stock prices. Our results show that positive changes of the tone affect positively stock prices in the Shanghai and the Shenzhen stocks markets. Additional extensions show that PBC communication does not have a persistent e ect on stock prices and that the tone of PBC communication still has a positive and significant impact on stock prices even when controlling for all the monetary policy instruments implemented by the central bank. Hence, our findings show that PBC communication matters as a monetary policy instrument to shape market expectations and to move asset prices.
URN:NBN:fi:bof-201904251162
Keywords: E52; E58; 330; Central Bank Communication; People's Bank of China Sentiment; Financial Markets